Thermodynamic Study of Polychlorinated Biphenyls Removal by Single-Walled Carbon Nanotube Nano-Sensor Based in Environment: DFT-NMR - Mahdavian, L. (Asian Journal of Chemistry, 2011)
In this study, we have conducted a thermodynamic investigation on converting polychlorinated biphenyls (PCBs) to 4-chlorobenzoic acid, 2-hydroxypenta-2 and 4-dienoic acid using nanosensor-based single-walled carbon nanotube (SWNT). Calculation were done using Gaussian program package. We employed the density functional-based NMR (DFT-NMR) and MNDO semi empirical methods. The polychlorinated biphenyls are one of the most persistent and widespread environmental pollutants. The goal of this work is to improve the detection of surface species of SWNT sensors under their working conditions and using computer calculations and to correlate the sensor signals with relative changes in electric resistance (Ω). We studied the structural and thermodynamic properties as well as the total energy of polychlorinated biphenyl absorption on SWNT at room temperature. When exposed to SWNT-based nanosensors, polychlorinated biphenyls are oxidized into other products including 4-chlorobenzoic acid and 2- hydroxypenta-2,4-dienoic acid. All the geometric structures of this conversion were optimized using B3LYP/6-31G**. Intermediates and transient states of them were optimized using density functional theory (DFT). The results obtained in present study show that electrical conduction and capacitance are increasing when polychlorinated biphenyl is near the surface and when converted to different products.